Employment Industry and Occupational Continuity in Germany: From the Nazi Regime to the Post-War Economic Miracle - Patrick A. Puhani (Institute for the Study of Labor (IZA), 2014)
Using retrospective survey data that covers 1939, 1950, 1960, and 1971, I compare individual-level changes in employment industry and occupational status in Germany from the beginning of World War II to the post-war reconstruction era dubbed the Economic Miracle (Wirtschaftswunder). This comparison reveals that, with only a few exceptions, labor allocation developments remained relatively stable even in the face of huge political and macroeconomic change.
Keywords: N34; J01; 330; employment; evolution; regime change; revolution; Germany; Arab Spring; Iraq